2003
DOI: 10.1046/j.1365-2141.2003.04067.x
|View full text |Cite
|
Sign up to set email alerts
|

Tandem transplants with different high‐dose regimens improve the complete remission rates in multiple myeloma. Results of a Grupo Español de Síndromes Linfoproliferativos/Trasplante Autólogo de Médula Ósea phase II trial

Abstract: Summary. Between 1994 and 1999, 88 multiple myeloma (MM) patients were included in a phase II study to evaluate a tandem autologous stem cell transplantation (ASCT) programme. The first was conditioned with melphalan 200 mg/m 2 (MEL200-ASCT1), and the second with cyclophosphamide, etoposide and BCNU (CBV-ASCT2). All patients were in response after MEL200-ASCT1. A control group of MM patients with response to a single ASCT was selected to compare outcomes. After MEL200-ASCT1, 26 patients (30%) achieved complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 24 publications
(39 reference statements)
3
23
1
Order By: Relevance
“…When we compared the survival of patients who underwent upfront single or tandem autologous SCT, tandem autologous SCT produced a longer OS compared with single autologous SCT (fig. 2b), also consistent with previous reports suggesting the superiority of tandem autologous SCT in MM treatment [16,17,18]. However, these data contrast with what was found in a recently published meta-analysis which showed that the use of tandem autologous SCT did not result in an improved OS in previously untreated MM patients [19].…”
Section: Discussioncontrasting
confidence: 55%
“…When we compared the survival of patients who underwent upfront single or tandem autologous SCT, tandem autologous SCT produced a longer OS compared with single autologous SCT (fig. 2b), also consistent with previous reports suggesting the superiority of tandem autologous SCT in MM treatment [16,17,18]. However, these data contrast with what was found in a recently published meta-analysis which showed that the use of tandem autologous SCT did not result in an improved OS in previously untreated MM patients [19].…”
Section: Discussioncontrasting
confidence: 55%
“…To improve the efficacy of the HDT maneuver itself, groups have explored the use of multiple cycles of HDT (tandem transplant; refs. [6][7][8], the use of combination chemotherapy conditioning regimens using agents in addition to or replacing melphalan in HDT conditioning (9)(10)(11)(12), and the addition of radiation therapy using targeted antibodies (13,14) or external beam radiation (15). Unfortunately, none of these approaches has been shown to be superior to the use of 200 mg/m 2 of melphalan.…”
mentioning
confidence: 99%
“…Barlogie et al [10,16] treated patients with ''Total Therapy (TT) 1,'' consisting of 2 cycles of highdose chemotherapy with tandem auto-PBSCT; they demonstrated its efficacy and safety, and achieved a high CR rate resulting in improvement of the prognosis. Tandem auto-transplantation has been reported in various countries [17][18][19]. In our protocol, as in TT 1, a VAD regimen containing no alkylating agents was used to reduce the tumor burden as induction therapy, followed by PBSC harvesting after HD-CY therapy and tandem auto-PBSCT with high-dose melphalan.…”
Section: Discussionmentioning
confidence: 99%